Pyridine‐functionalized fullerene derivative as an independent electron transport layer enabling efficient and hysteresis‐free regular perovskite solar cells - Ye Wang (Wiley-VCH, 2021)
Abstract Suitable electron transport materials bearing good interfacial contact, improved electron transport ability, and matched energy levels are indispensable for developing efficient perovskite solar cells (PSCs). Herein, regular (n‐i‐p) planar Cs0.05FA0.83MA0.12PbI2.55Br0.45 (CsFAMA) PSC devices were fabricated using a pyridine‐functionalized fullerene derivative (C60‐3‐BPy) as an independent electron transport layer (ETL), delivering a decent power conversion efficiency (PCE) of 18.22%, which is dramatically higher than that of the control device based on [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) ETL (15.70%). The energy level offset between C60‐3‐BPy and the perovskite is smaller than that based on PCBM ETL, which is beneficial for efficient ohmic contact in ETL/perovskite interface and improved open‐circuit voltage (Voc). Moreover, C60‐3‐BPy affords strong coordination interactions with perovskite, leading to an improved film quality of the perovskite layer with enlarged grain size and decreased trap state density, which contribute to facilitated electron extraction as reflected by the increases of both the fill factor (FF) and the short‐circuit current (Jsc). C60‐3‐BPy‐facilitated electron extraction further results in hysteresis‐free devices.